2010
DOI: 10.4315/0362-028x-73.10.1858
|View full text |Cite
|
Sign up to set email alerts
|

A Prolonged Outbreak of Salmonella Montevideo Infections Associated with Multiple Locations of a Restaurant Chain in Phoenix, Arizona, 2008

Abstract: An outbreak of Salmonella serotype Montevideo infections associated with multiple locations of restaurant chain A in Phoenix, AZ, was identified in July 2008. One infected individual reported eating at a chain A catered luncheon where others fell ill; we conducted a cohort study among attendees to identify the vehicle. Food and environmental samples collected at six chain A locations were cultured for Salmonella. Restaurant inspection results were compared among 18 chain A locations. Routine surveillance ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…in food products, including beef, chicken, pork and their by products, seafood, eggs, dairy products, fresh produce, chocolate, breakfast cereals, snacks and almonds, peanut butter, infant formula, and pet treats (Beuchat & Mann, 2010;Guan, Chen, & Hoover, 2005;Jin et al, 2008;Mahmoud, 2009Mahmoud, , 2010aMahmoud, , 2010bMahmoud, Vaidya, Corvalan, & Linton, 2008;Meyer, Thiel, Ullrich, & Stolle, 2010;Patel et al, 2010;Podolak, Enache, Stone, Black, & Elliott, 2010). The wide variety of products shows that Salmonella is able to grow and survive in a large range of conditions even low moisture and thermal processing.…”
Section: Salmonellamentioning
confidence: 99%
See 1 more Smart Citation
“…in food products, including beef, chicken, pork and their by products, seafood, eggs, dairy products, fresh produce, chocolate, breakfast cereals, snacks and almonds, peanut butter, infant formula, and pet treats (Beuchat & Mann, 2010;Guan, Chen, & Hoover, 2005;Jin et al, 2008;Mahmoud, 2009Mahmoud, , 2010aMahmoud, , 2010bMahmoud, Vaidya, Corvalan, & Linton, 2008;Meyer, Thiel, Ullrich, & Stolle, 2010;Patel et al, 2010;Podolak, Enache, Stone, Black, & Elliott, 2010). The wide variety of products shows that Salmonella is able to grow and survive in a large range of conditions even low moisture and thermal processing.…”
Section: Salmonellamentioning
confidence: 99%
“…In the United States, Salmonella has been the culprit for almost one and a half million reported infections, causing thousands of hospitalizations and hundreds of deaths each year (Jin et al, 2008;Patel et al, 2010). Food-borne outbreaks in the United States have an annual cost of around $7 billion (Pathania, McKee, Bilgili, & Singh, 2010).…”
Section: Salmonellamentioning
confidence: 99%
“…Previous research revealed that overall restaurant evaluation during health department routine inspections was not predictive of the likelihood of foodbome illness (6,12,18). However, certain violations were more likely to be identified during inspections of restaurants that had confirmed foodbome illness outbreaks (19).…”
mentioning
confidence: 95%
“…As salmonellae are ubiquitous in the environment, they are common causative agents of food poisoning. Foodborne illnesses caused by Salmonella are common in the United States and in many European countries, and have always been a significant health burden worldwide (Allos, Moore, Griffin, & Tauxe, 2004;Bäumler, Hargis, & Tsolis, 2000;Brands et al, 2005;Busani et al, 2005;Davies & Wales, 2010;Magnino et al, 2009;Patel et al, 2010). The most recent analysis of epidemiologic data on foodborne disease outbreaks in the United States indicated that Salmonella was the most common bacterial etiologic agent, accounting for 112 (52%) outbreaks attributed to bacteria (CDC, 2009).…”
mentioning
confidence: 99%